To insist on presence – Attempts at theatrical and pedagogical invention in social distance (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
The theatrical practice experience had to adapt to atypical sites and different plans of action, due to the necessary social distancing in the pandemic context. The article explores pedagogical and artistic attempts realized through students in graduate classes at a public university, based on different perspectives, and developed from the creative initiative in live events as an object of study and connection to the audience. Preferably to the analytical approach, the choice is to consider words and themes that came into view during the work in class resulting from the remote circumstances, as a way to introduce an initial consideration on the challenges and uncertainties of the theatrical creation.
Keywords: Theatre; Creative process; Pedagogy of theatre; Art in the pandemic context